Sočinenija v 12-i t.t. [Pod red. A.S. Erusalimskogo] (Izd-vo AN SSSR)
1. Pod red. B.F. Poršneva. Sost. A.V. Paevskaja i A.G. Černov. 1957. XL, 772 str. 2. Pod red. A.Z. Manfreda. Sost. A.V. Paevskaja i A.G. Černov. 1957. 750 str. 3. Pod red. A.Z. Manfreda. 1958. 654 str. 4. Pod red. A.Z. Manfreda i B.F. Poršnev. 1958. 768 str. 5. Pod red. V.M Chvostova. 1958. 596 str. 6. Pod red. E.A. Želubovskoj. 1959. 816 str. 7. Pod red. M.V. Nečkinoj. 1959. 868 str. 8. Pod red. N.M. Družinina. 1959. 563 str. 9. Pod red. A.S. Erusalimskogo. 1961. 884 str. 10. Pod red. B.B. Kafengauzoj, M.I. Michajlova i N.I. Pavlenko. 11. Pod red. N.M. Družinina. 1959. 628 str. 12. Pod red. A.S. Erusalimskogo. 1962. 536 str. S bibliogr., ill-mi, prt-mi, tab-mi i ukaz.